A dual-cycling fluorescence scheme for ultrasensitive DNA detection through signal amplification and target regeneration. Issue 8 (7th March 2019) - Iwe, Idorenyin A.; Li, Zhigang; Huang, Jiahao
Abstract : Ultrasensitive DNA detection through dual-cycling, fluorescence amplification mechanisms. Abstract : In this work, we propose an ultrasensitive fluorescence strategy for DNA detection. This method utilizes a molecular beacon (MB), a hairpin probe (HP), and an enzyme to trigger dual-cycling reactions (cycles I and II). In cycle I, the target is repeatedly used to amplify the fluorescence emission through hybridizations with the MB and cleavage reactions achieved by the enzyme. In cycle II, hybridization reactions between the HP and a segment of the MB continuously regenerate the target to trigger more cycle I reactions, leading to an enhanced fluorescent signal. The detection limit of the method is determined to be as low as 50 fM within 45 min, which is 2 to 3 orders of magnitude lower than that of the conventional fluorescence strategies. The method also shows a high selectivity over mismatched and random DNA sequences. The signal amplification mechanism of the strategy offers insights into constructing efficient and ultrasensitive biosensors for various applications.